The Role of Online Tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this paper, the changes in tourism industry caused by the introduction of Internet technology and advantages and disadvantages of using the Internet in contemporary business travel agencies were analyzed. Through this work, the impact of the Internet technology on marketing activities of contemporary travel agencies was also analyzed.